Comparison of Efficacy of Once-Weekly Trelagliptin versus Once-Daily Vildagliptin on Glycemic Control in Patients with Type 2 Diabetes: A Randomized Controlled Trial - Nazeer, Adeela; Khan, Jamal Azfar; Younus, Mohammad Imran (Indus Journal of Bioscience Research, 2025)
Background and Objective: The comparative efficacy of once-weekly trelagliptin versus once-daily vildagliptin in glycemic control among patients with type 2 diabetes remains insufficiently explored. This study aimed to evaluate the efficacy of these two DPP-4 inhibitors in improving glycemic outcomes in individuals inadequately controlled on metformin. Material and Methods: A randomized controlled trial was conducted at Department of General Medicine, PNS Hafeez Hospital Islamabad. Adults aged 30–60 years with type 2 diabetes and baseline HbA1c of 7.5–9.5% were enrolled using non-probability consecutive sampling. Participants were randomized via lottery to receive either trelagliptin 100 mg once weekly or vildagliptin 50 mg once daily for three months. Baseline demographics, comorbidities, and laboratory values were recorded. The primary outcome was the proportion of patients achieving HbA1c <7% at three months; secondary outcomes included mean reduction in HbA1c. Data were analyzed using t-tests and chi-square tests, with stratification for potential confounders. Results: Of 102 participants, both groups were similar in baseline characteristics. At three months, the mean HbA1c was 7.6 ± 0.7% in the trelagliptin group and 7.3 ± 0.6% in the vildagliptin group (p < 0.05). Mean reduction in HbA1c was 0.8 ± 0.3% for trelagliptin and 1.0 ± 0.4% for vildagliptin (p < 0.01). Achievement of HbA1c <7% occurred in 19 (37.3%) versus 28 (54.9%) participants, respectively (p < 0.1). No statistically significant differences were observed in subgroup analyses. Conclusion: Vildagliptin provided greater improvement in glycemic control compared to trelagliptin. Both agents were safe and effective in routine clinical practice.